Braconidae (Hymenoptera) in the collection of the Institute of Zoology, NAS of the Azerbaijan Republic. Part I. Subfamilies Doryctinae, Rogadinae, Braconinae (Hymenoptera). - Abdinbekova, Arifa; Huseynova, Ellada; Kerimova, Ilhama (Contributions to Entomology = Beiträge zur Entomologie, 2010)
The paper gives some faunistic records of the braconids from Subfamilies Doryctinae, Rogadinae, Braconinae from the collection of the institute of Zoology of the National Academy of Sciences of Azerbaijan located in Baku. For each taxon localities in Azerbaijan, distribution and hosts remarks are given.